1976
DOI: 10.1037/0022-006x.44.3.480
|View full text |Cite
|
Sign up to set email alerts
|

Case study: Use of covert self-instruction for the elimination of psychotic speech.

Abstract: A covert self-instructional program was used to reduce the frequency of a hospitalized chronic schizophrenic's inappropriate verbalizations, A marked reduction in the frequency of the target behavior accompanied the treatment intervention, and improved verbal behavior was directly responsible for the decision to discharge the subject from the hospital. At a 6-month follow-up, inappropriate verbalization continued at low rates, the subject remained out of the hospital, and he was employed part-time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1978
1978
1993
1993

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Self-talk or self-instruction has been used in cases of thought-disordered or delusional speech. Meyers, Mercatoris, and Sirota (1976), in a carefully designed single-case study with a 47-year-old male diagnosed with chronic undifferentiated schizophrenia, reported marked reduction of inappropriate verbalisation which was maintained at 6-month's follow-up. The client was taught, by various modelling procedures, to use appropriate self-instruction before responding to questions from others (e.g., "I won't ramble on", "I must pay attention to what people say").…”
Section: Single-case Studiesmentioning
confidence: 96%
“…Self-talk or self-instruction has been used in cases of thought-disordered or delusional speech. Meyers, Mercatoris, and Sirota (1976), in a carefully designed single-case study with a 47-year-old male diagnosed with chronic undifferentiated schizophrenia, reported marked reduction of inappropriate verbalisation which was maintained at 6-month's follow-up. The client was taught, by various modelling procedures, to use appropriate self-instruction before responding to questions from others (e.g., "I won't ramble on", "I must pay attention to what people say").…”
Section: Single-case Studiesmentioning
confidence: 96%
“…The success of the selfinstructional approach was replicated by Meyers, Mercatoris, and Sirota (1976), but was not supported in a separate study by Margolis and Shemberg (1976). As early as 1973, .Meichenbaum and Cameron demonstrated that a cognitive self-instructional program which trains schizophrenic patients to talk to themselves is effective in modifying their behaviour on a variety of attentional, thinking, and language tasks, resulting in an overall increase in patient self-control.…”
Section: Thought Disordersmentioning
confidence: 97%
“…As early as 1973, .Meichenbaum and Cameron demonstrated that a cognitive self-instructional program which trains schizophrenic patients to talk to themselves is effective in modifying their behaviour on a variety of attentional, thinking, and language tasks, resulting in an overall increase in patient self-control. The success of the selfinstructional approach was replicated by Meyers, Mercatoris, and Sirota (1976), but was not supported in a separate study by Margolis and Shemberg (1976).…”
Section: Thought Disordersmentioning
confidence: 97%
“…Operant conditioning paradigms informed the cognitive modification procedures of Wagner (1968) and Meiselman (1973), and both of these researchers reported improvement on attentional measures in their experimental groups as a result of their procedures. Meichenbaum and Cameron (1973, 1974), Meyers, Mercatoris, and Sirota (1976), and Bradshaw (1982) emphasized cognitive-behavioral self-instructional techniques, also with impressive results. Margolis and Shemberg (1976), however, failed in their attempted replication of the Meichenbaum and Cameron (1973) study.…”
Section: Cognitive Rehabilitation Approaches With Patients With Schiz...mentioning
confidence: 99%